Association between nut consumption and mortality among Chinese older people: A national cohort study based on CLHLS from 2008 to 2018 - He, Dengxin; Huangfu, Zheng; Pan, Minghao (Frontiers in Nutrition, 2022)
Background Few quantitative studies have explored the associations between nut consumption and better health outcomes among a national cohort of community-dwelling older Chinese people. Given the need for more evidence to support the health benefits of nuts among Chinese people, we investigated whether nut consumption was associated with subsequent 10-year mortality. Methods We analyzed data from the Chinese Longitudinal Healthy Longevity Survey. The data on nut consumption at baseline were collected using a questionnaire through face-to-face interviews. The vital status and date of death were ascertained by a close family member or village doctor of the deceased participant during the follow-up survey. Cox analyses were performed to explore the association between nut consumption and mortality. Subgroup analyses by age group (< 80 or ≥ 80 years), sex (male/female), activities of daily living (impaired or normal), and physical exercise(yes or no) were performed to assess whether the association between nut consumption and mortality differed across different populations. Result The median survival time was 1,302 days for the 11,915 participants with complete information of survival time and nut consumption. The association between nut consumption and mortality was significant after the adjusting for significant factors in the univariate Cox analyses. The hazard ratios were lower in male participants, those who were < 80 years old, and those who did not engage in physical exercise at baseline. The association between nut consumption and mortality was not significant among participants with normal activities of daily living. Conclusion The association between nut consumption and mortality was not significant among participants who had normal activities of daily living but was significant among participants who had impaired activities of daily living. Including nuts in the diets cloud help to extend the lifespan in older Chinese people, especially those with impaired activities of daily living.